Real life application of soft computing - Shukla, Anupam , 1965-; Kala, Rahul; Tiwari, Ritu , 1977- (Boca Raton, Florida : CRC Press/Taylor & Francis Group, 2010)
The application of soft computing techniques in industrial control, security, data mining, software world, robotics, can be easily seen. This book uncovers such applications, explaining the underlying technology and its implementation. It demonstrates how they can be modeled, designed, and implemented
"An Auerbach book."
Includes bibliographical references and index
Keywords: Soft computing